Optimización de la producción en el volumen de ventas en la panadería “CRONST PAN “periodo 2018 - Coro Caín, Efraín (2019)
The present work, OPTIMIZATION OF HTE PRODUCTION IN THE VOLUME OF SALES OF THE BAKERY CRONST-PAN PERIOD 2018, establish is an analysis of the production of the company and its incidence in the volume of sales within the province of Chimborazo. Today, in this globalized world, the only constant changes, efficiently satisfying the needs of customers has become a real challenge. Achieving competitive advantage in organizations depends in large part on their ability to operate effectively in dimensions such as cost, quality, speed, Innovation, and flexibility, in order to adapt to changes in market demand. Production cost are determined when the resources invested are used at a given level of optimization, the, it turns out that when productivity increases, cost decrease, these are part of the working methods, which help to give practical knowledge. At the same time, they provide guidelines that are considered necessary for the best performance and strengthening of tasks in orderly, organized and planned manner. With the present research, I hope to contribute to the improvement of Cronst-pan, marking known to its manager and administrators the application of specific key points to reach a competitive level within the market that is more demanding every day with the optimization mainly based on the product that allows it to be an optimal and efficient bakery in each one of its work areas in order to improve its profitability.